Measuring media-based social interactions in online civicmobilization against corruption in Brazil - Gomes, Alan Keller; Pimentel, Maria da Graça Campos (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
Given the importance of new media on traditional forms of civic mobilization, it is opportune to investigate how online civic mobilization can be described in terms of the actions performed by users. In earlier work we proposed the application of established data mining procedures to evaluate rules associated with social interactions, and developed a technique for codifying, mining and evaluating social interactions. In this paper we present a method which guides the iterative application of the technique. We used the method to analyze social interactions in two online civic mobilizations against corruption occurred in Brazil. After two iterations, the results include: in terms of generic social interactions, Facebook users are more likely to perform Likes and Comments on Posts; in terms of media-based social interactions, users are more likely to choose the media text.